Quantitative reduction in short-chain fatty acids, especially butyrate, contributes to the progression of chronic kidney disease. (10th September 2019) - Wang, Siqi; Lv, Dan; Jiang, Shuanghong; Jiang, Jianpin; Liang, Min; Hou, Fanfan; Chen, Ye
Abstract : Chronic kidney disease (CKD) affects 10–15% of the population worldwide, results in high morbidity and mortality, and requires costly treatment and renal replacement therapy. Glomerulosclerosis, tubulointerstitial fibrosis, and persistent intestinal flora disturbance are common in CKD. Short-chain fatty acids (SCFAs), produced by the intestinal microbiota, have been previously reported to ameliorate kidney injury; however, the specific concentrations and types that are required to improve renal function remain unknown. The present study aims to evaluate the levels of SCFAs in healthy and CKD patients, and to test the hypothesis that SCFAs play a critical role in delaying CKD progression. One hundred and twenty-seven patients with CKD and 63 healthy controls from China were enrolled in the present study. Butyrate, which is considered beneficial to humans, was almost three-times higher in healthy volunteers than that in CKD5 subjects ( P =0.001). Moreover, the serum SCFA levels in controls were significantly higher than that in CKD patients ( P <0.05), and the butyrate level among CKD5 patients (1.48 ± 0.60 μmol/l) was less than half of that in controls (3.44 ± 2.12 μmol/l, P <0.001). In addition, we observed an inverse correlation between butyrate level and renal function ( P <0.05). A CKD rat model transplanted with microbiota obtained from CKD patients exhibited accelerated CKD progression via increased production of trimethylamine N-oxide (TMAO), which was reversed by supplementation with extra butyrate. Our results showed that SCFA levels were reduced in CKD patients and that butyrate supplementation might delay CKD progression.